Mechanisms of Mouse Neural Precursor Expansion after Neonatal Hypoxia-Ischemia - Buono, Krista D. (J Neurosci, 2015)
Neonatal hypoxia-ischemia (H-I) is the leading cause of brain damage resulting from birth complications. Studies in neonatal rats have shown that H-I acutely expands the numbers of neural precursors (NPs) within the subventricular zone (SVZ). The aim of these studies was to establish which NPs expand after H-I and to determine how leukemia inhibitory factor (LIF) insufficiency affects their response. During recovery from H-I, the number of Ki67(+) cells in the medial SVZ of the injured hemisphere increased. Similarly, the number and size of primary neurospheres produced from the injured SVZ increased approximately twofold versus controls, and, upon differentiation, more than twice as many neurospheres from the damaged brain were tripotential, suggesting an increase in neural stem cells (NSCs). However, multimarker flow cytometry for CD133/LeX/NG2/CD140a combined with EdU incorporation revealed that NSC frequency diminished after H-I, whereas that of two multipotential progenitors and three unique glial-restricted precursors expanded, attributable to changes in their proliferation. By quantitative PCR, interleukin-6, LIF, and CNTF mRNA increased but with significantly different time courses, with LIF expression correlating best with NP expansion. Therefore, we evaluated the NP response to H-I in LIF-haplodeficient mice. Flow cytometry revealed that one subset of multipotential and bipotential intermediate progenitors did not increase after H-I, whereas another subset was amplified. Altogether, our studies demonstrate that neonatal H-I alters the composition of the SVZ and that LIF is a key regulator for a subset of intermediate progenitors that expand during acute recovery from neonatal H-I.